Internet and wireless security - Temple, Robert 1963-; Regnault, John (Institution of Engineering and Technology, 2002)
The book reviews developments in the following fields: XML security mechanism; security modelling language; public key infrastructures; identifier-based public key cryptography; secure digital archiving of high-value data; wireless security; TETRA security; mobile environment adaptation; ignite managed firewall; VPN service; information assurance; biometrics; virtual world; human-computer interaction; and security management standard.